ANALISIS PENGARUH BESAR BUTIRAN AGREGAT KASAR TERHADAP KUAT TEKAN BETON NORMAL - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
The purpose of this research is to know whether the influence of bulk aggregate grains influence the targeted compressive strength value, test sample to concrete compressive strength. This research is a quantitative research that starts from the testing of materials used as concrete materials and make the concrete mix design based on the procedure to make normal concrete on SNI 03-2834-2000. The analyzing data using simple statistical method by comparing the average value of compressive strength from various sample forms. From the result of analysis, obtained data from of compressive strength achieved with the bulk of the granular aggregate grains used differently. The coarse aggregate grain also affects the compressive strength value with the greater tendency of coarse aggregate grains used, the greater the compressive strength.